PENENTUAN KADAR RESIDU TETRASIKLIN HCl PADA IKAN AIR TAWAR YANG BEREDAR DI PASAR SEGIRI MENGGUNAKAN METODE SPEKTROFOTOMETRI ULTRA VIOLET - Henny Nurhasnawati; Siti Jubaidah; Novita Elfia (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
Tetracycline HCl is one of the most commonly used antibiotics in fish farming that aims to control diseases caused by bacteria. The purpose of this study was to determine the presence and the level of tetracycline HCl antibiotic residue in freshwater fishes sold at the Segiri traditional market. The method used in this research was a standard addition ultraviolet spectrophotometry. The results showed that residue level of tetracycline HCl in freshwater fish is 192,067 μg/g – 257,409 μg/g. These result was far exceeded the maximum residue level of tetracycline class antibiotics in meat and dairy based on SNI 01-6366-2000 that limit the residue not higher than 0.1 μg/g